JOURNAL OF GOVERNMENT & POLITICS : Local Good Governance Sustainability: Roles of Civil Society in Surakarta City, Indonesia - Teguh Yuwono (FISIPOL UMY, 2016)
Civil society role is often seen as less powerfull agent in forming or maintaining good governance than two dominant agents (state and private actors).